Analysis of the influence of external and internal factors on stock prices (Case study on the Infobank15 index) - Nikmah, Karimatun; Novianti, Tanti; Ardiansyah, Ferry (International Journal Labs, 2025)
In the era of globalization, the capital market plays an important role in the economy, especially in Indonesia, which has experienced an increase in the number of investors by 17.19% in 2023. This study aims to analyze the factors that affect the stock price of the banking sector in Indonesia during the period 2018 to 2023. The method used is secondary data analysis from the annual financial statements obtained from the Indonesia Stock Exchange, with a purposive sampling technique to select 13 banking companies as a sample. The analysis for the difference test in comparing changes in stock prices from the period before the pandemic, during pandemic and pasca pandemic using the Anova and Kruskal Wallis tests and the panel data test to evaluate the influence of macroeconomic variables and fundamental factors on stock prices. The results of the Anova and Kruskall Wallis test show that almost all companies tested had differences in stock prices pra-pandemic, during pandemic and pasca pandemic. The results data panel show that interest rate variables, NIM, CAR, NPL, ROE, BOPO, LDR, and PBV have a significant influence on stock prices, while GDP, Inflation, EPS, and PER have no effect. The study found that interest rates have a positive effect, while NPLs and BOPO have a negative impact on stock prices. The study’s implications emphasize the importance of bank management to pay attention to fundamental and external factors, especially interest rates and financial ratios, to increase investor attractiveness and stock price stability in the capital market.